Sosialisasi Pemanfaatan Tanaman Obat Keluarga untuk Kesehatan Tulang dan Otot serta Ergonomi Bagi Lansia di Rt 004/09, Kelurahan Meruya Utara, Jakarta Barat - Babay Jutika Cahyana; Chriswahyudi Chriswahyudi; Rini Yanuarti; Nurfitriyana Nurfitriyana; Ekadipta Ekadipta; Andri Arthono; Abdul Gofar S; Rindu DS Pitaloka (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
Humans will experience old age or old age (elderly) where when in that phase there will be a decrease in muscle mass so that it will affect the mobility of the elderly. Socialization of medicinal plants (TOGA) and ergonomics of movement for the elderly is knowledge provided for the elderly who live in Meruya Utara Village, especially in RT 004/09, where the number of elderly is quite large. This socialization is expected to help improve the knowledge and understanding of the elderly regarding the benefits of family medicinal plants and ergonomics of movement problems. The explanation of the use of TOGA plants that is conveyed is mainly related to the processing of TOGA, especially those that have properties for bone and muscle health where there are various types of TOGA that can maintain bone and muscle health such as ginger, temulawak, celery, and lemongrass. The explanation of ergonomic movement is conveyed starting from the type of elderly, problems faced, elderly diseases, safe activities for the elderly and a focus on rearranging the bathroom which is an area prone to frequent accidents for the elderly where the elderly bathroom must at least have a sitting toilet, railing, water reservoir, rough bathroom floor and a door handle with a handle